Emotional functioning in people with traumatic brain injuries (TBI). - Masilela, Clifford Thulani (My University, 1999)
This study investigated the emotional functioning of people who had been diagnosed as having traumatic brain injuries (TBI) of the frontal lobes. This was done with a view to examining whether there were changes in the emotional functioning of people with TBI in the period following their injuries. The pre-injury (or premorbid) emotional functioning of the respondents with TBI was assessed retrospectively through self-reports, which were compared with the ratings by the primary and secondary care-givers of these respondents. The current (post-injury) emotional functioning of the participants with TBI was also assessed through self-reports and the ratings by the primary and secondary care-givers. (abbreviation abstract)
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Arts in Clinical Psychology
Keywords: Brain damage -- Patients -- Mental health.; Brain damage -- Psychological aspects.